2011
DOI: 10.3189/172756411795931769
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal characterization of sea-ice deformation

Abstract: In late March 2007 an array of GPS ice drifters was deployed in the Beaufort Sea as part of the Sea Ice Experiment: Dynamic Nature of the Arctic (SEDNA). The drifters were deployed in an array designed to resolve four, nested spatial scales of sea-ice deformation, from 10 to 140 km, with the arrays maintaining appropriate shape for strain-rate calculation until mid-June. In this paper, we test whether sea-ice deformation displays fractal properties in the vicinity of SEDNA. We identify that deformation time se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
116
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 22 publications
19
116
0
Order By: Relevance
“…The role of forcing (wind stress) and coastline geometry in establishing coherence in lead patterns/fractures in the ice cover captured by sea ice deformation has also been explored in past studies (Overland et al, 1995;Hutchings et al, 2005Hutchings et al, , 2011. Overland et al (1995) demonstrated that in the Beaufort Sea for spatial scales: (i) exceeding 100 km the sea ice cover moves as an aggregate; (ii) less than 100 km the ice cover moves as an aggregate or discrete entity; and (iii) on the order of 1 km the ice cover is characterized by floe (ice-ice) interactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of forcing (wind stress) and coastline geometry in establishing coherence in lead patterns/fractures in the ice cover captured by sea ice deformation has also been explored in past studies (Overland et al, 1995;Hutchings et al, 2005Hutchings et al, , 2011. Overland et al (1995) demonstrated that in the Beaufort Sea for spatial scales: (i) exceeding 100 km the sea ice cover moves as an aggregate; (ii) less than 100 km the ice cover moves as an aggregate or discrete entity; and (iii) on the order of 1 km the ice cover is characterized by floe (ice-ice) interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined sea ice drift and deformation response to atmospheric forcing and coastline geometry on varying timescales (Overland et al, 1995;Richter-Menge et al, 2002;Geiger and Perovich, 2008;Hutchings et al, 2011). In an assessment of springtime sea ice drift in a region to the west of the Antarctic Peninsula, Geiger and Perovich (2008) identified low-frequency motion in response to atmospheric forcing and coastal geometry associated with regional-scale transport and higher-frequency near-inertial oscillatory motion associated with mixing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased drift and deformation rates from 1979 to 2009 were found in the central Arctic and have been attributed to sea-ice kinematics and accompanying reduction in ice cover strength (Rampal et al 2009). Hutchings et al (2011) demonstrated coherence in deformation over length scales exceeding 100 km on daily to weekly timescales. Hutchings & Rigor (2012) further demonstrated a transition to a younger, thinner ice cover in the Beaufort Sea region associated with a change in ice-drift regimes in the western Arctic and Beaufort Sea since 1998.…”
mentioning
confidence: 99%
“…Recent Lagrangian analyses have also used buoy trajectories to quantify sea-ice drift and deformation (Rampal et al 2008;Rampal et al 2009;Hutchings et al 2011;Weiss 2013). Spatial and temporal scaling laws illustrated coupling in space and time in sea-ice deformation processes (Rampal et al 2008).…”
mentioning
confidence: 99%